2008
DOI: 10.1585/pfr.3.s1027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rotating Magnetic Islands Driven by External Perturbation Fields in the TU-Heliac

Abstract: A new method for rotating magnetic islands by external perturbation fields is proposed. In the experiments, perturbation fields were produced using four pairs of cusp field coil, in which alternating currents having a π/2 phase shift flowed. A phase shifter for the coil currents was designed and constructed. The phase difference in the floating potential signals measured using two Langmuir probes confirmed that the magnetic islands rotated in the counterclockwise direction (c/cw). The clockwise (cw) rotation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(16 reference statements)
0
3
1
Order By: Relevance
“…2. The perturbation field coil current I ex was three times greater than that in the previous rotating island experiment [5].…”
Section: External Perturbation Coilscontrasting
confidence: 54%
See 2 more Smart Citations
“…2. The perturbation field coil current I ex was three times greater than that in the previous rotating island experiment [5].…”
Section: External Perturbation Coilscontrasting
confidence: 54%
“…1. We have explored the possibility of the poloidal rotation of islands by changing the phase of each perturbation coil current [5]. In this experiment, to study the island structure located at fixed poloidal positions, we used only two pairs of external perturbation field coils at the toroidal angles φ = 90 • and 270 • .…”
Section: External Perturbation Coilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vacuum field calculations showed that the perturbation field produced by these coils can produce the m = 3 magnetic island at a rational flux surface. By using alternative currents and phase control in the perturbation field coil current, these coils can produce a rotating magnetic island [10]. In this experiment, to study the relationship between plasma flow and magnetic island at a fixed poloidal position, we used only two pairs of external perturbation field coils at toroidal angles φ = 0 • and 180 • .…”
Section: External Perturbation Fieldmentioning
confidence: 99%